Situation Report: Czechoslovakia, 31 January 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Dogma Write Large Soviet Oil Deliveries in 1983 A Profile of Industrial Management Official Anger at Appointment of Exile Bishops Miscellaneous